2015
DOI: 10.1186/s13567-015-0216-x
|View full text |Cite
|
Sign up to set email alerts
|

A combinational approach of multilocus sequence typing and other molecular typing methods in unravelling the epidemiology of Erysipelothrix rhusiopathiae strains from poultry and mammals

Abstract: Erysipelothrix rhusiopathiae infections re-emerged as a matter of great concern particularly in the poultry industry. In contrast to porcine isolates, molecular epidemiological traits of avian E. rhusiopathiae isolates are less well known. Thus, we aimed to (i) develop a multilocus sequence typing (MLST) scheme for E. rhusiopathiae, (ii) study the congruence of strain grouping based on pulsed-field gel electrophoresis (PFGE) and MLST, (iii) determine the diversity of the dominant immunogenic protein SpaA, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
61
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 62 publications
10
61
1
1
Order By: Relevance
“…In this study, the mammalian spaA‐ positive isolates demonstrated the widest range of virulence factor profiles. In agreement with previous publications, these isolates were uniformly positive for all tested virulence factors, except algI (94.1%), dnaB (94.1%) and mviN1 (23.5%; Janßen et al., ). In contrast, there is limited documentation of virulence factor profiles for SpaB‐ and SpaC‐positive isolates.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the mammalian spaA‐ positive isolates demonstrated the widest range of virulence factor profiles. In agreement with previous publications, these isolates were uniformly positive for all tested virulence factors, except algI (94.1%), dnaB (94.1%) and mviN1 (23.5%; Janßen et al., ). In contrast, there is limited documentation of virulence factor profiles for SpaB‐ and SpaC‐positive isolates.…”
Section: Discussionsupporting
confidence: 92%
“…In E. rhusiopathiae strains, no correlation has been found between multilocus sequence typing and PFGE (10). The results of this study also showed no clear correlations between the geographic origins or years of isolation of the strains and the PFGE patterns.…”
Section: Discussionmentioning
confidence: 39%
“…However, Janßen et al (10) reported that among 165 E. rhusiopathiae field isolates primarily from Germany, only 2.4% (4/165) were of the M203/I257-SpaA type (grouped as group V in their study). Furthermore, we did not find this SpaA type in the 135 E. rhusiopathiae isolates collected from livestock and wildlife from multiple continents (16), including the isolates from arctic and boreal ungulates (21) ( Table S4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesized that this ability to persist in the environment for extended periods, in addition to E. rhusiopathiae 's wide host range, are the most important factors facilitating its widespread distribution (Brooke and Riley, 1999). Several virulence factors have been demonstrated or suggested for this bacterium, including neuraminidase, surface protective antigen A and the capsular polysaccharide (Ogawa et al, 2011; Shi et al, 2012), the majority of which appear to be commonly present (Janßen et al, 2015). Isolates of E. rhusiopathiae sequenced to date fall into three distinct clades, all of which appear to have retained some degree of host generalism (Forde et al, 2016), suggesting that most strains can likely be transmitted between species.…”
Section: Introductionmentioning
confidence: 99%